Heavy metal alarm of marine fish consumption surrounding Qiongzhou Strait, the South China Sea - Zhang, Peng; Ye, Zijun; Huang, Liping; Wang, Xuefeng; Zhang, Wei (Frontiers in Marine Science, 2025)
Heavy metal pollution presents a significant concern in marine ecosystems, posing a serious threat. Monitoring the levels of heavy metals in marine fish is crucial for safeguarding human health. This study specifically investigates the bioaccumulation of eight elements (arsenic (As), cadmium (Cd), chromium (Cr), copper (Cu), nickel (Ni), lead (Pb), selenium (Se), and zinc (Zn)) in marine fish in the Qiongzhou Strait in the South China Sea. Zn emerged as the predominant heavy metal, with an average concentration of 39.5 μg/g. Most marine fish showed a low risk of heavy metal intake, Pampus argenteus exhibited the lowest risk at 10–6. Moreover, caution is advised regarding the consumption of Uroconger lepturus due to its elevated risk of As bioaccumulation, with levels reaching 70.1 μg/g, contributing significantly to the total target hazard quotient at 94.3% (3.64). This study provides valuable recommendations for coastal environmental protection and the prevention of ecological incidents.